2012
DOI: 10.5812/hepatmon.6099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin, Pioglitazone, and Silymarin Treatment on Non- Alcoholic Fatty Liver Disease: A Randomized Controlled Pilot Study

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is one of the most common reasons of enzyme increase in liver. In About 10 percent of patients with NAFLD, the disease progresses toward Non Alcoholic Steatohepatitis (NASH) and about one third of them may progress toward cirrhosis, liver dysfunction, and even hepatocellular carcinoma.ObjectivesAccording to high prevalence of NAFLD and the fact that there is no consensus on treatment of this disease, the aim of this study was to assess the effects of metformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 15 publications
7
49
0
4
Order By: Relevance
“…Several groups have been interested in examining the potential of silymarin in the treatment of NAFLD/ NASH. In three comparative trials silymarin has been tested against placebo, in one against vitamin E, and in one against pioglitazone and metformin (Summary in Table 4, [98][99][100][101][102]). Furthermore, three Italian groups conducted open trials applying silymarin combined with other agents (see Additional file 3).…”
Section: Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Several groups have been interested in examining the potential of silymarin in the treatment of NAFLD/ NASH. In three comparative trials silymarin has been tested against placebo, in one against vitamin E, and in one against pioglitazone and metformin (Summary in Table 4, [98][99][100][101][102]). Furthermore, three Italian groups conducted open trials applying silymarin combined with other agents (see Additional file 3).…”
Section: Clinical Datamentioning
confidence: 99%
“…Although the number of participants, doses and period of treatment were different, both trials revealed a tendency to reduce ALT/ AST levels in silymarin treated patients [99,101]. In comparison to pioglitazone and metformin, silymarin also caused a more significant change in ALT/AST levels [102]. However, the effect of silymarin on triglycerides, fasting blood sugar, and insulin levels was rather weak compared to pioglitazone treatment [102].…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, rosiglitazone, a PPARγ agonist, in combination with fenofibrate, a PPARα agonist, was in clinical trial, but owing to the small number of participants, the clinical trial was terminated (33). Currently, among many thiazolidinediones, pioglitazone is the only drug that is considered to be an effective therapeutic agent for improving NAFLD (34). Pioglitazone, in combination with Berberine (a plant alkaloid that lowers cholesterol), is in Phase II clinical trial.…”
Section: Role Of Nuclear Receptors In Hepatic Lipid/glucose Metabolismmentioning
confidence: 99%
“…Yağ depolanmasına ilave olarak başlayan inflamasyonu, giderek şiddetlenen ileri inflamasyon ve balonlaşma dejenerasyonu takip eder. Bu süreç devam ederse; fibroz, mallory cisimciği ve sirozu takiben karaciğer yetmezliği gelişir (4,5).…”
Section: Patogenezunclassified